Asuhan Keperawatan Pada Tn.U Dengan Diagnosa Medis Congestive Heart Failure - Rizki Dian Cahyawati; Endah Sari Purbaningsih; Sumarni; Dikha Sazilli; Mahendra (MEJORA Medical Journal Awatara, 2024)
The World Health Organization (WHO) in 2016 showed that in 2015 there were 23 million or around 54% of total deaths caused by Congestive Heart Failure (CHF). Based on a doctor's diagnosis, the prevalence of heart failure is around 1.5% or 29,550 people. Meanwhile, according to diagnosis or symptoms, the estimated number of heart failure sufferers is 0.4% or around 29,880 people. CHF, commonly known as congestive heart failure, is the heart's inability to pump adequate blood to meet the tissue's need for oxygen and sufficient nutrients, causing cardiac output that should be normal to decrease and causing chest pain. This study aims to determine nursing care for CHF patients in the ICCU room at Rsu Gunung Jati, Cirebon City. After applying nursing care to patient Mr. U using a case study method consisting of assessment, nursing diagnosis, intervention, implementation and evaluation which was carried out for 2 days. The results showed that the nursing diagnosis of decreased cardiac output was partially resolved, the problem of gas exchange disorders was resolved, and the final diagnosis, namely anxiety, was resolved on day 2 of treatment.